Evaluation Of Different Components Against Xanthomonas Axonopodis Pv. Malvacearum (Journal of Plant Disease Sciences, 2023)
Bacterial blight is a destructive foliar disease causes severe yield reduction in cotton cultivation. Bacterial blight caused by bacterial plant pathogen Xanthomonas axonopodis pv. malvacearum. The paper disc method was used to assess the sensitivity of various chemicals, bioagents, and botanicals against Xanthomonas axonopodis pv. malvacearum. Among the chemicals, Streptomycine sulphate + Tetracycline (Streptocycline) 250 ppm demonstrated the greatest inhibition zone (15.34 mm). Among the antagonistic organism such as Pseudomonas fluorescens was found significantly superior to record the maximum inhibition zone (17.30 mm). The 15% leaf extract of Neem was found to be significantly superior to the other botanicals tested, recording the highest zone of inhibition (12.0 mm).
Keywords: Bioagents; Botanicals; Chemicals; Xanthomonas axonopodis pv. malvacearum